Combined effects of five prothrombotic genotypes and cancer on the risk of a first venous thromboembolic event - Skille, Hanne; Paulsen, Benedikte; Hveem, Kristian; Gabrielsen, Maiken Elvestad; Brumpton, Ben Michael; Hindberg, Kristian; Gran, Olga Vikhammer; Rosendaal, Frits Richard; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Journal of Thrombosis and Haemostasis, 2020)
Background - The role of combined prothrombotic genotypes in cancer‐related venous thromboembolism (VTE) is scarcely studied. We aimed to investigate the impact of a 5‐single nucleotide polymorphism (SNP) score on the risk of VTE in patients with and without cancer using a population‐based case‐cohort. Methods - Cases with a first VTE (n = 1493) and a subcohort (n = 13 072) were derived from the Tromsø Study (1994‐2012) and the Nord‐Trøndelag Health Study (1995‐2008). Five SNPs previously reported as a risk score were genotyped: ABO (rs8176719), F5 (rs6025), F2 (rs1799963), FGG (rs2066865), and F11 (rs2036914). Hazard ratios (HRs) for VTE were estimated according to cancer status and the number of risk alleles in the 5‐SNP score (0‐1, 2‐3, and ≥4 alleles). Results - During a median follow‐up of 12.3 years, 1496 individuals were diagnosed with cancer, of whom 232 experienced VTE. The VTE risk increased with the number of risk alleles in the 5‐SNP score among subjects without and with cancer. In cancer‐free subjects, the HR was 2.17 (95% confidence interval [CI] 1.79‐2.62) for ≥4 versus 0‐1 risk alleles. In cancer patients, the corresponding HR was 1.93 (95% CI 1.28‐2.91). The combination of cancer and ≥4 risk alleles yielded a 17‐fold (HR 17.1, 95% CI 12.5‐23.4) higher risk of VTE compared with cancer‐free subjects with 0‐1 risk alleles. Conclusion - The risk of VTE increases with the number of prothrombotic risk alleles in subjects with and without cancer, and the combination of prothrombotic risk alleles and cancer leads to a highly elevated risk of VTE.